Distinct expression profile reveals glia involvement in the trigeminal system attributing to post-traumatic headache - Gurueswar Nagarajan; Yumin Zhang (The Journal of Headache and Pain)
Abstract Background Post-traumatic headache (PTH) is a common comorbid symptom affecting at least one-third of patients with mild traumatic brain injury (mTBI). While neuroinflammation is known to contribute to the development of PTH, the cellular mechanisms in the trigeminal system crucial for understanding the pathogenesis of PTH remain unclear. Methods A non-invasive repetitive mTBI (4 times with a 24-h interval) was induced in male mice and effect of mTBI was tested on either bregma or pre-bregma position on the head. Periorbital allodynia and spontaneous pain behavior were assessed using von Frey test and grimace score, respectively. Quantitative PCR was used to assess extent of mTBI pathology. RNA sequencing was performed to obtain transcriptomic profile of the trigeminal ganglion (TG), trigeminal nucleus caudalis (Sp5C) and periaqueductal gray (PAG) at 7 days post-TBI. Subsequently, quantitative PCR, in situ hybridization and immunohistochemistry were used to examine mRNA and protein expression of glia specific markers and pain associated molecules. Results The repetitive impacts at the bregma, but not pre-bregma site led to periorbital hypersensitivity, which was correlated with enhanced inflammatory gene expression in multiple brain regions. RNA sequencing revealed mTBI induced distinct transcriptomic profiles in the peripheral TG and central Sp5C and PAG. Using gene set enrichment analysis, positive enrichment of non-neuronal cells in the TG and neuroinflammation in the Sp5C were identified to be essential in the pathogenesis of PTH. In situ assays also revealed that gliosis of satellite glial cells in the TG and astrocytes in the Sp5C were prominent days after injury. Furthermore, immunohistochemical study revealed a close interaction between activated microglia and reactive astrocytes correlating with increased calretinin interneurons in the Sp5C. Conclusions Transcriptomics analysis indicated that non-neuronal cells in peripheral TG and successive in situ assays revealed that glia in the central Sp5C are crucial in modulating headache-like symptoms. Thus, selective targeting of glia cells can be a therapeutic strategy for PTH attributed to repetitive mTBI.